PUSAT PELATIHAN SEPAK TAKRAW BANUA ANAM DI KANDANGAN - Anwar, Muhammad Fuadi; Huzairin, Muhammad Deddy (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2024)
Sports is growing every year, including takraw. In South Kalimantan, especially in Banua Anam, sepak takraw is growing. This development needs to be supported by a training center. The Banua Anam Sepak Takraw Training Center has a problem about how to design a sepak takraw training center based on a sepak takraw training program. Programmatic methods are used in design to identify problems so as to produce concepts. The concept of Functional Programming is obtained after going through identification with a programmatic method. These concepts and methods were chosen to produce a functional design based on the athlete's training program and daily activities.